CONGENITAL GENETIC DISORDER: MEDICAL AND SOCIAL ASPECTS OF DOWN SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Down syndrome (trisomy 21) is a genetic disorder caused by an extra chromosome in the 21st pair of chromosomes. This syndrome leads to delays in intellectual and physical development, distinctive facial features, and other health issues. Prenatal tests are available for early detection of the condition, and early interventions can improve the development of patients. The article provides information about the diagnosis, development, and treatment methods of Down syndrome.